Method to Assess Computerised Systems Supporting Maintenance Services - Michał Pająk; Bogdan Landowski; Łukasz Muślewski; Dragutin Lisjak (Tehnički Glasnik)
There are many CMMS (Computerized Maintenance Management Systems) systems on the market in a wide range of prices and capabilities. An important problem for enterprise decision-makers is the selection of a system supporting maintenance services, appropriate for the specificity of the enterprise. The study presents an analysis of methods for assessing and selecting this type of systems and proposes a subjective-point method for analysing this type of issues. The issues presented in the study are part of the work on the development of materials and tools supporting enterprise decision-makers in the process of analysing existing solutions and selecting IT systems supporting maintenance services. Additionally, survey research was carried out, which enabled the generation of a database of basic values for the features of selected products, evaluation criteria, and in particular the determination of weight values for individual criteria, which contributed to the automatic execution of calculations for the adopted assumptions.